BUSINESS ANALYSIS OF AMONIATION AND FERMENTATION PALM OIL FRONDS AS A SUBSTITUTION OF FORAGE ON ACEH CATTLE IN KECAMATAN SELESAI - Henrico Fermi Ginting; Edhy Mirwandhono; Tri Hesti Wahyuni; Ma'ruf Tafsin; Nurzainah Ginting (Universitas Sumatera Utara, 2017)
ABSTRACT. The experiment was conducted in Kecamatan Selesai from June to August 2016. The method used was survey method with consideration of the aceh cattle studies using palm oil fronds in amoniation and fermentation as a substitution of forage in Kecamatan Selesai, with the division of business scale. Criteria for determining the scale of business was based on the number of livestock ownership. Determination limit frequency distribution length of the class, was the ownership of the largest ownership reduced smallest in the length of class. The result showed that every treatments P0, P1, P2, P3 provide different results to average of total cost production (Rp/ekor/peroide): P0 6.284.187,69, P1 Rp. 6.502.768,02, P2 Rp. 6.225.270,04, and P3 Rp. 6.459.359. The average of total cost production (Rp/ekor/periode): P0 Rp. 6.430.300,00, P1 Rp. 6.688.470,00, P2 Rp. 6.666.010,00,- and P3 Rp. 6.666.010. The average of analysis profit/loss(Rp/ekor/periode): P0 Rp. 146.112,31; P1 Rp. 185.701,98, ; P2 Rp.440.739,96 dan P3 Rp.190.940,20. The average of R/C ratio: 1,02; 1,03; 1,07 dan 1,03. The Average of IOFC (Rp/ekor/periode): 197.687,31; 240.356,98; 490.354,96 and 242.515,20. The results of this research was utilization of palm oil fronds which treated phisical + fermentation can increase income of cattle raiser.